2018
DOI: 10.1177/1356336x18785053
|View full text |Cite
|
Sign up to set email alerts
|

How trainee physical education teachers in England write, use and evaluate lesson plans

Abstract: Traditionally, all physical education initial teacher training (PEITT) courses in England, and in many other countries, require trainee teachers to complete detailed lesson plans for each lesson they teach in their school-based practicum and then to evaluate those lessons. However, there has been a limited amount of research on lesson planning in PEITT generally or in England specifically. The purpose of this study therefore was to gain an initial insight into how trainee physical education teachers write, use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Instead, the plan has to provide the Accounting teacher with a general outline of their teaching goals, learning objectives and means of accomplishing them. This supports a study conducted by Capel, Bassett, Lawrence, Newton, and Zwozdiak-Myers (2019) on how trainee teachers write, use and evaluate their lesson plans. The researchers found that most trainees stated they found the lesson plan helpful in the lesson.…”
Section: Discussionsupporting
confidence: 86%
“…Instead, the plan has to provide the Accounting teacher with a general outline of their teaching goals, learning objectives and means of accomplishing them. This supports a study conducted by Capel, Bassett, Lawrence, Newton, and Zwozdiak-Myers (2019) on how trainee teachers write, use and evaluate their lesson plans. The researchers found that most trainees stated they found the lesson plan helpful in the lesson.…”
Section: Discussionsupporting
confidence: 86%
“…One participant believed that lesson plans written in unit plans would have been more useful for her and would be more useful long term. According to Capel et al (2018), lesson planning can take between 30 minutes and an hour and a half for one lesson. This is a substantial time investment for a curriculum document if it is not useful for the present teacher (if the teacher is only writing a lesson in order to tick a box) or future teachers.…”
Section: Challenges To Developing Curriculum In An International Schoolmentioning
confidence: 99%
“…In the initial training of PE teachers, in addition to the specific contents of the discipline, it is necessary to intentionally address a diversity of methodological aspects that are transferable to the classroom in which they carry out their professional activity (Capel et al, 2018). These are related to the design of classes, the organization of groupings, time management or the application of assessment.…”
Section: Cooperative Learning As An Essential Element In the Initial mentioning
confidence: 99%